The Financial Impact of Drug Proliferation on Public Budgets(A Comparative Study) - ad-bsj, ad-bsj (Basra studies journal, 2025)
The proliferation of narcotics constitutes a serious financial and legal challenge that places a heavy burden on public budgets. Expenditures are spread across security, judicial, and correctional institutions, in addition to the costs of treatment and rehabilitation. This research examines the financial impact of narcotics in Iraq and Egypt by analyzing national legislation and the legal sanctions established to combat drug-related offenses, as well as evaluating the effectiveness of these measures in safeguarding public funds and reducing financial waste. The study employs a comparative analytical approach to the relevant legal provisions, aiming to uncover strengths and weaknesses in the existing legislation and to propose reforms that enhance the efficiency of public spending while maintaining a balance between the requirements of criminal deterrence and financial stability.